Effect of vaginal estrogen on pessary use. Issue 9 (September 2016) - Dessie, Sybil; Armstrong, Katherine; Modest, Anna; Hacker, Michele; Hota, Lekha
Abstract Introduction and hypothesis Many providers recommend concurrent estrogen therapy with pessary use to limit complications; however, limited data exist to support this practice. We hypothesized that vaginal estrogen supplementation decreases incidence of pessary-related complications and discontinuation. Methods We performed a retrospective cohort study of women who underwent a pessary fitting from 1 January 2007 through 1 September 2013 at one institution; participants were identified by billing code and were eligible if they were postmenopausal and had at least 3 months of pessary use and 6 months of follow-up. All tests were two sided, andP values < 0.05 were considered statistically significant. Results Data from 199 women were included; 134 used vaginal estrogen and 65 did not. Women who used vaginal estrogen had a longer median follow-up time (29.5 months) compared with women who did not (15.4 months) and were more likely to have at least one pessary check (98.5 % vs 86.2 %, P < 0.001). Those in the estrogen group were less likely to discontinue using their pessary (30.6 % vs 58.5 %, P < 0.001) and less likely to develop increased vaginal discharge than women who did not [hazard ratio (HR) 0.31, 95 % confidence interval (CI) 0.17–0.58]. Vaginal estrogen was not protective against erosions (HR 0.93, 95 % CI 0.54–1.6) or vaginal bleeding (HR 0.78, 95 % CI 0.36–1.7). Conclusions Women who used vaginal estrogen exhibited a higher incidence of continued pessary use and lower incidence of increased vaginal discharge than women who did not.